(untitled) (Bangladesh Journal of Pharmacology, 2015)
The Forced Swim Test (FST) is a rodent behavioral paradigm utilized for assessment of potential antidepressant-like medications. In this model the mice are put in a plexiglas tank. The tank is loaded with water and the behavior of the mice to escape the tank is scored. The behavioral parameter scored in this test is called immobility, resembling a behavioral state of misery, as seen in human depression. Video Clip of Methodology: Pre-experiment: 50 sec Full Screen Alternate Experiment: 7 min 12 sec Full Screen Alternate